Literasi Kesehatan Dalam Pencegahan Covid-19 (Studi Kasus Unilak) - Hidayat, Rahmad; Rismayeti, Rismayeti; Amelia, Vita (Jurnal FPPTI, 2022)
The aims of this study to determine the level of health literacy of lecturers and employees at Lancang Kuning University, one of the steps in preventing covid-19, in addition to studying the behavior in implementing health protocols for awareness of the importance of preventing covid-19. This study uses a quantitative descriptive method with a population of 420 respondents and a sample of 80 respondents. This study instrument use a questionnaire that has been tested for validity with a total of 30 questions with a Cronbach alpha result of 0.926, there are 3 indicators in this study, namely functional health literacy, interactive health literacy and critical health literacy. The results of this study from those 3 indicators, functional health literacy by 72%, interactive health literacy 76% and critical health literacy 77% overall the level of health literacy of Lancang Kuning University lecturers and employees is 76% in the 76%-100% range. which is included in the very good category. This means that the health literacy of Lancang Kuning University lecturers and employees is very good.  Keywords: Health literacy, covid-19; health literacy level; health protocol; lecturers and employees.